Morphofunctional Organization of the Connections From the Medial and Intermediate Parts of the Central Nucleus of the Amygdala Into Distinct Divisions of the Lateral Hypothalamic Area in the Rat - Barbier, Marie; Fellmann, Dominique; Risold, Pierre-Yves (Frontiers in Neurology, 2018)
Projections from the central nucleus of the amygdala (CEA) into the lateral hypothalamic area (LHA) show a very complex pattern. After injection of an anterograde tracer (Phaseolus vulgaris leucoagglutinin – PHAL) into several parts of the CEA, we observed that projections converged onto the caudal lateral LHA but provided distinct patterns in rostral tuberal regions. These projections were compared to that of neurons containing the peptides ‘melanin-concentrating hormone’ (MCH) or hypocretin (Hcrt). Because the distribution of these neurons is stereotyped, it was possible to characterize distinct divisions into the LHA. Some of them in the rostral tuberal LHA (the dorsal (LHAd) and suprafornical regions (LHAs)) received a distinct innervation by projections issued from neurons in respectively anterior or posterior regions of the medial part (CEAm) or from the rostral pole of the lateral part of the CEA part (CEAla) of the CEA. Therefore, this work illustrates that projections from the CEAm and CEAla converge into the caudal lateral LHA but diverge into the rostral tuberal LHA.